What Happened - Hillary Rodham Clinton (Simon & Schuster Paperbacks, 2017)
What Happened is a 2017 memoir by Hillary Clinton about her experiences as the Democratic Party's nominee and general election candidate for President of the United States in the 2016 election. Published on September 12, 2017, it is her seventh book with her publisher, Simon & Schuster